A review of the geographical distribution of Sphaenorhynchus prasinus Bokermann, 1973 (Anura: Hylidae) in the state of Alagoas, northeastern Brazil - de Araujo Vieira, Katyuscia (2016)
Sphaenorhynchus prasinus is a neotropical small greenish treefrog characterized by a canthal black line, dermal folds on forearms and tarsi, dermal fold on elbow and round calcar appendage, and a white dermal flap with round lateral margins on the subcloacal region. Its geographic distribution comprises southeastern and northeastern of Brazil. In this note, we rectify the previous records of S. prasinus and restablish the occurrence of the species for the state of Alagoas, northeastern Brazil based on new findings.